Employment prospects and firm-based training : evidence from opening the Swiss-German border - Neuber-Pohl, Caroline [Verfasser]; Pregaldini, Damiano [Verfasser]; Backes-Gellner, Uschi [Verfasser]; Dummert, Sandra [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2026)
"We study how improved wage opportunities for skilled workers affect firm-based training, using the 2002 opening of the Swiss labor market to German commuters as a natural experiment. The reform triggered a large outflow of skilled workers from German border regions, prompting firms to expand apprenticeship training. Using a Difference-in-Differences approach, we find a significant increase in the number of apprenticeships in affected firms in Germany despite unchanged apprentice wages. This pattern is consistent with an outward shift in apprentice supply: higher wages for skilled workers across the border made apprenticeships more attractive to young people. Our findings suggest that improvements in skilled workers’ wage prospects, rather than adjusting apprentice pay, may help to address training gaps and alleviate skill shortages." (Author's abstract ; BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; G 1.3.1.1 Ausbildungsstellenmarkt; G 1.2.3.2 Anforderungen & Bedarfe; S 3.2 Unternehmen und Behörden; I 2.2.1 Westeuropa; 370; 330; Betriebliche Berufsausbildung; Arbeitsmarkt; Ausbildungsstellenmarkt; Arbeitskräfteangebot; Arbeitsmigration; Fachkräftemangel; Einflussfaktor; Ausbildungsverhalten; Ausbildungsbereitschaft; Ausbildungsplatzangebot; Grenzgebiet; Bundesrepublik Deutschland; Schweiz